Pendampingan Peningkatan Kompetensi Profesional Guru PAI melalui Metode STEAM di SMP Plus Al-Qodiri Jember - Muhamad Ansori (LP3M IAIFA Kediri, 2023)
A good teacher is a teacher who is able to carry out his duties properly, in this case a teacher must understand and carry out various kinds of competencies that exist and must be achieved by a teacher. One of the competencies that must be possessed by teachers is professional competence, which means that a teacher must have a broad and deep mastery of learning materials so that learning can run well and achieve learning objectives. At the SMP Plus Al-Qodiri institution, PAI teachers hone students' cognitive abilities still using classical methods, so that sometimes learning is still centered on the teacher and students get bored easily and learning and teaching activities are less effective. Therefore, one of the efforts to create creative, innovative, comfortable, and enjoyable learning is the Professionalism Training and Assistance for teachers through STEAM. STEAM stands for Science, Technology, Engineering, Art, and Mathematics. The approach in this assistance applies the Asset Based Community Development approach. The ABCD approach is a service method that seeks to develop an Asset-Based Community (potential), in which case the assets developed are asset teachers. Implementation of empowerment through five stages, namely the stages of Define, Discovery, Dream, Design and Deliver. The result of this assistance is the development of the quality of human resource assets for PAI teachers at SMP Plus Al-Qodiri Jember in creating and implementing STEAM in learning, so as to create active, effective, efficient, innovative and systematic learning in the classroom.